2021
DOI: 10.1038/s41598-021-89448-1
|View full text |Cite
|
Sign up to set email alerts
|

Total nitrogen is the main soil property associated with soil fungal community in karst rocky desertification regions in southwest China

Abstract: Karst rocky desertification (KRD) is a type of land deterioration, resulting in the degraded soil and a delicate ecosystem. Previous studies focused on the influence of KRD on the animals and plants, the impact of KRD on microorganisms, especially soil fungi remains to be discovered. This study reveals the change in the soil fungal community in response to KRD progression in southwest China. Illumina HiSeq was used to survey the soil fungal community. Results showed that the soil fungal community in the severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…The effects of total nitrogen on fungal community composition are similarly well documented (Cline et al 2018;Xiao et al 2020;Moore et al 2021;Qi et al 2021;He et al 2021). Total nitrogen was the major driver in fungal community composition along a deserti cation gradient, accounting for 43% of the variation in community composition (Qi et al 2021). Fungal communities are also heavily involved in nitrogen cycling and thus can change nitrogen availability.…”
Section: Plant Height Is An Important Determinant Of Microbial Commun...mentioning
confidence: 84%
“…The effects of total nitrogen on fungal community composition are similarly well documented (Cline et al 2018;Xiao et al 2020;Moore et al 2021;Qi et al 2021;He et al 2021). Total nitrogen was the major driver in fungal community composition along a deserti cation gradient, accounting for 43% of the variation in community composition (Qi et al 2021). Fungal communities are also heavily involved in nitrogen cycling and thus can change nitrogen availability.…”
Section: Plant Height Is An Important Determinant Of Microbial Commun...mentioning
confidence: 84%
“…Moreover, in heavy RD areas, the soil fungal community differs significantly from other degrees of RD, with soil total nitrogen being the main factor correlated with fungal communities, followed by pH [16]. The phylum Ascomycota is the most abundant in non-degraded soils, while Basidiomycota dominates in severe RD soils, and the ratio of Ascomycota to Basidiomycota decreases significantly with the deepening of RD, which can serve as an indicator of the degree of RD [16]. In the degraded karst ecosystems, a study has shown that soil degradation in the karst region reduced soil bacterial genetic diversity and significantly changed community structure [17].…”
Section: Introductionmentioning
confidence: 93%
“…In fact, the bacterial diversity slightly increases and the richness slightly decreases in severe RD areas. Moreover, in heavy RD areas, the soil fungal community differs significantly from other degrees of RD, with soil total nitrogen being the main factor correlated with fungal communities, followed by pH [16]. The phylum Ascomycota is the most abundant in non-degraded soils, while Basidiomycota dominates in severe RD soils, and the ratio of Ascomycota to Basidiomycota decreases significantly with the deepening of RD, which can serve as an indicator of the degree of RD [16].…”
Section: Introductionmentioning
confidence: 96%